EVALUATION of moving objects' navigation parameters UNDER multimode - A. S. Benkafo; A. A. Lobaty (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
On the basis of the theory of systems of random structure, the problem of interconnecting the inertial navigation system and satellite navigation system with identification modes and optimal estimator outputs meters is investigated.